Effects of the pitch configuration design on players’ physical performance and movement behaviour during soccer small-sided games - Coutinho, Diogo (2019)
This study aimed to identify the effects of different pitch configurations on youth players positional and physical performances. Forty players participated in a Gk + 5vs5 + Gk small-sided game under four conditions: regular condition (regular), pitch with the direction of competitive matches; sided condition (sided), goals were changed to width; different pitch orientation (≠orientation), performed in side-to-side line compared to competitive matches; dynamic pitch (dynamic), boundaries were randomly changed every minute by: regular pitch; decrease 6 m width; diamond shape. The following variables were considered: players' effective playing space, distance between teammates' dyads time spent synchronized, average speed and a ratio between the distance covered at different intensities and distance covered while recovering. Overall, players exhibited better performances in pitches that are more representative of the environmental information seen during competitive matches (regular and ≠orientation). However, coaches may also use different boundary conditions to promote the players' ability to adapt to different context information.